Prevalence, Predictive Factors, and Characteristics of Osteoporosis in Hyperthyroid Patients - Ayotunde O. Ale; Anthonia O. Ogbera; Henry O. Ebili; Olusola L. Adeyemo; Taiwo O. Afe (International Journal of Endocrinology)
Objective. The osteoporosis in thyroid disorder has the lowest report especially in sub-Saharan Africa. This study aims to determine the prevalence, predictive factors, and characteristics of osteoporosis in hyperthyroid patients. Method. Forty (40) hyperthyroid patients and healthy controls ages 21–50 years were recruited in this study. Questionnaires were administered to capture bio- and clinical data. Biochemical tests included blood, thyroid functions, intact parathyroid hormone, corrected calcium, and 25-hydroxyvitamin D tests. Bone mineral density (BMD) was also evaluated. Data were analyzed using the SPSS 21. A p value < 0.05 was regarded as significant. Results. Osteoporosis was observed in 18 (45%) of study subjects, 13 (72.2%) females and 5 (27.8%) males, respectively. The BMD of the hyperthyroid patients had a negative correlation with free triiodothyronine, FT3 (r=−0.49, p=0.005), FT4 (r=−0.33, p=0.009), corrected calcium (r=−0.31, p=0.039), alkaline phosphatase (r=−0.53, p<0.001), and osteocalcin (r=−0.61, p<0.001). Conversely, a positive association with thyroid-stimulating hormone (TSH) (r=0.54, p<0.001) was observed. Multiple regression showed osteocalcin (p<0.001) and TSH (p=0.015) as independent predictors of osteoporosis. Conclusion. Thyrotoxicosis is a risk factor for osteoporosis occurrence, and we recommend routine screening for this bone disease in persons over 20 years old with this disorder.